The Renoprotective Actions of Peroxisome Proliferator-Activated Receptors Agonists in Diabetes - M. C. Thomas; K. A. Jandeleit-Dahm; C. Tikellis (PPAR Research)
Pharmaceutical agonists of peroxisome proliferator-activated receptors (PPARs) are widely used in the management of type 2 diabetes, chiefly as lipid-lowering agents and oral hypoglycaemic agents. Although most of the focus has been placed on their cardiovascular effects, both positive and negative, these agents also have significant renoprotective actions in the diabetic kidney. Over and above action on metabolic control and effects on blood pressure, PPAR agonists also appear to have independent effects on a number of critical pathways that are implicated in the development and progression of diabetic kidney disease, including oxidative stress, inflammation, hypertrophy, and podocyte function. This review will examine these direct and indirect actions of PPAR agonists in the diabetic kidney and explore recent findings of clinical trials of PPAR agonists in patients with diabetes.